Estimating Egyptsat -1 Radiometric Coefficient using Cross Calibration with Spot4 and Spot5 - Abdo, Sayed; Ziedan , Ibrahim; Elyamany, Asmaa (International Journal of Electrical and Computer Engineering Systems, 2023)
The pre-processing of satellite data is a vital step in harnessing the full potential of remote sensing pictures. EgyptSat-1, Egypt’s first satellite for observing the Earth from a distance, encountered a major obstacle as a considerable amount of the images it captured could not be used since the necessary radiometric coefficients were missing. This study utilises a cross-calibration methodology, taking advantage of the spectral similarity between Spot 4 and Spot 5 as reference satellites, in order to retrieve these difficult-to-obtain coefficients. The analysis demonstrates that the selection of window size in the cross-calibration process is crucial in determining the outcomes. In general, smaller window sizes tend to produce better results. However, there are certain cases when larger windows are more successful, such as in the scenario of EgyptSat-1’s band 3 and its cross-calibration with Spot 5. In contrast to a previous study, the new methodology produces much diminished uncertainty factors, indicating a remarkable enhancement in accuracy. The cross-calibration results highlight the significance of selecting the appropriate window size and satellite for accurate calibration, especially for the Near-Infrared (NIR) band, which is highly responsive to these parameters. Moreover, there are differences in the computations of offset and gain between Spot 4 and Spot 5, which further highlight the intricacies involved in radiometric calibration. The results of this study lead to the determination of improved calibration coefficients for EgyptSat -1, with the specific aim of maximising the accuracy of the results and minimising any errors.